Synthesis of butenolides by reactions of 3‐alkenoic acids with diphenyl sulfoxide/oxalyl chloride. (9th August 2018) - Ding, Rui; Li, Yaxi; Liu, Yongguo; Sun, Baoguo; Yang, Shaoxiang; Tian, Hongyu
Abstract: Butenolides are of high interest as potential flavouring compounds. Efficient and general methods for the production of these compounds remain to be developed. A series of butenolides were prepared starting from 3‐alkenoic acids with diphenyl sulfoxide/oxalyl chloride, followed by treatment with bases. The 3‐alkenoic acids with alkyl substitutents on the double bond were converted into the corresponding 2‐butenolides with yields of greater than 77%, whereas those with aryl groups on the double bond produced the corresponding 3‐butenolides with yields of about 80%. The butenolides were produced by β eliminations of the corresponding chlorolactones, which were generated from the chlorolactonization of 3‐alkenoic acids. The chlorodiphenylsulfonium salt produced from the reaction between diphenyl sulfoxide and oxalyl chloride was supposed to be the chlorinating reagent for the chlorolactonization. This is a very simple and convenient method for the preparation of butenolides. Abstract : Butenolides are of high interest as potential flavoring compounds. Efficient and general methods for their production are still needed to be developed. A series of butenolides were prepared starting from 3‐alkenoic acids with diphenyl sulfoxide/oxalyl chloride followed by treatment with bases. The 3‐alkenoic acids with alkyl substitutents on the double bond were converted into the corresponding 2‐butenolides in more than 77% yields, whereas those with aryl groups on the double bond produced the corresponding 3‐butenolides in about 80% yields. The butenolides were produced by β eliminations of the corresponding chlorolactones, which were generated from the chlorolactonization of 3‐alkenoic acids. The chlorodiphenylsulfonium salt produced from the reaction between diphenyl sulfoxide and oxalyl chloride was supposed to be the chlorinating reagent for the chlorolactonization. It is a very simple and convenient method for the preparation of butenolides.